PENGARUH SHIFT KERJA, BEBAN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. NUSAJAYA PERSADATAMA MANDIRI KABUPATEN MOROWALI - Rizki, Selvi Diliyanti; Aswawi, Nurafiah; Makmur, Muhammad Rizaldi; Aisyah, Nur (Unitri Press, 2023)
This research aims to analyze the influence of work shifts, workload and incentives on employee performance at PT Nusajaya Persadatama Mandiri district. Morowal. The population in this study were all employees of PT. Nusajaya Persadatama Mandiri, totaling 200 people using the proportional random sampling method which was calculated using the Slovenian formula with an error rate of 10%, resulting in a sample of 67 respondents. The data collection method is by distributing questionnaires to respondents. The data analysis technique in this research uses multiple linear regression using the SPSS version 20 program. The results of this research show that: (1) work shifts, workload and incentives simultaneously have a positive and significant effect on employee performance, (2) shift work has a negative effect and significant on employee performance, (3) workload has a positive and significant effect on employee performance and (4) incentives have a positive and insignificant effect on employee performance.